ANALYSIS OF NATURAL TOURISM POTENTIAL OF SEMANGAT GUNUNG VIILAGE KARO REGENCY, NORTH SUMATERA WITH QUANTITATIVE QUALITATIVE DESCRIPTIVE METHOD - Sherly Ennina Maretha Sinuraya; Titien Suryanti Rostian; R L Pangaribowo (Journal of Synergy Landscape, 2022)
A brief, clear and comprehensive summary of the contents of the article containing :North Sumatra Province has natural, cultural, historical and culinary tourism resources well-known at home and abroad. There are many natural and cultural attractions which is the advantage of North Sumatra Province, one of the regencies located in North Sumatra, has a very interesting landscape for it’s culture and nature, namely Karo Regency.One of the villages in Karo Regency, North Sumatra has a various natural and cultural attraction, namely Desa Semangat Gunung, among others the state of the flora and fauna of an area with natural landscape such as forests, mountains, and so on which includes the physical condition of an area. How is the potential for natural tourism which if found in the Desa Semangat Gunung with qualitative descriptive method techniques quantitative?This study aims to analyze the natural tourism potential of Desa Semangat Gunung as tourism villages. The method used in this research is descriptive quantitative qualitative. The tools and materials used are hardware such as laptops, writing, software such as miscrosoft, photoshop, autocad and etc.The results of this study plan Desa Semangat Gunung as a tourism village based on nature tourism by looking at visuals the existing landscape in the village area Keywords: analysis of the potential for natural tourism, tourist villages, mountain spirit villages, disticts karo